Technology and The North American Forest - Brown, Marian (Scientia Canadensis, 1992)
ABSTRACTThis paper is a critical review of recent historical literature relating to nineteenth and twentieth-century European-based technology in the North American forest. My discussion is limited to the industrial technologies of logging, sawmilling, pulp and paper milling, and forestry. These technologies will be discussed with reference to three issues in the history of technology: first, the nature of technological change; second, the environmental and social impacts of technology; and finally, the role of social values in determining choices of technology. Throughout, there will be an attempt to compare Canadian and American perspectives, when these diverge.